Pelatihan Penetapan Sistem Informasi Akuntansi untuk Pengambilan Keputusan Manajerial di CV. Fajar Anugrah Persada Kota Semarang - Ahmad Muhid; K. Emi Trimiati; Wahyu Tri Astuti; Raden Rara Ayu Widaningsih (Politeknik Piksi Ganesha Indonesia, 2025)
This study aims to analyze the effectiveness of implementing an Accounting Information System (AIS) in improving the quality of managerial decision-making at CV. Fajar Anugrah Persada. Utilizing a structured assistance method, this research explores the transformation from conventional recording systems to the digitalization of financial reporting. The results indicate that AIS implementation significantly accelerates the reporting cycle and provides accurate data for management in operational strategies. These findings confirm that AIS quality is positively correlated with successful strategic decision-making and overall organizational efficiency. The digitalization of financial information has proven to be a determinant variable in strengthening the company's competitiveness in a dynamic market.